2012
DOI: 10.3897/natureconservation.3.3732
|View full text |Cite
|
Sign up to set email alerts
|

“Mind the gap!” – How well does Natura 2000 cover species of European interest?

Abstract: Setting aside protected areas is widely recognized as one of the most effective measures to prevent species from extinction. Accordingly, there has been a tremendous effort by governments worldwide to establish protected areas, resulting in over 100,000 sites, which are set aside, to achieve the 10% target proposed at the Fourth World Park Congress in 1992 in Caracas. The main effort of the European Union to achieve this target is the Natura 2000 network of protected areas, comprising over 25,000 sites represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 30 publications
4
64
0
Order By: Relevance
“…The Natura 2000 network is governed by the Directive 79/409/EEC, adopted in April 1979 for the conservation of wild birds (also called "Birds Directive") and the Directive 92/43/EEC, adopted in May 1992 for the conservation of natural habitats, wild fauna and flora (also called "Habitats Directive"). Even if the Natura 2000 network is a European network of natural and semi-natural sites with high heritage values due to the exceptional flora and fauna they contain, the effectiveness of this network still remains unclear (Gruber et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Natura 2000 network is governed by the Directive 79/409/EEC, adopted in April 1979 for the conservation of wild birds (also called "Birds Directive") and the Directive 92/43/EEC, adopted in May 1992 for the conservation of natural habitats, wild fauna and flora (also called "Habitats Directive"). Even if the Natura 2000 network is a European network of natural and semi-natural sites with high heritage values due to the exceptional flora and fauna they contain, the effectiveness of this network still remains unclear (Gruber et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While the designation of SPAs is based on the presence of bird species listed in the annexes of the Birds Directive, including a validation stage of the EU, SACs designation (Habitats Directive) is more complex and involves several stages (Evans 2012). Nationally, Natura 2000 sites are selected on the basis of national lists proposed by the member states.…”
Section: Introductionmentioning
confidence: 99%
“…Protected areas vary widely between and within countries and regions, and the varying characteristics include the institution date, conservation focus, effective level of protection, permanence of protection, constancy of protection, ecological scale of protection, type of management, management authority and reference legislation, to cite some of them. In addition, the effectiveness of the selection process and the resulting Natura 2000 network have often been questioned because each country made its designations largely independently, and the designation of sites has been criticised as depending too strongly on governmental politics, economic and cultural criteria, and interactions between society and the environment Fenu et al, 2017;Gruber et al, 2012;Orlikowska et al, 2016;Trochet and Schmeller, 2013). In addition, in their analysis, Trochet and Schmeller (2013) demonstrated that the Natura 2000 network also covers species not listed in the annexes of the Habitats Directive, at least in the case of mammals, birds and reptiles; this might happen also for plants.…”
Section: Discussionmentioning
confidence: 99%
“…2.2 Importance of Natura 2000 for taxa Gruber et al (2012) devised a representation index (REX), in which he calculates the representation proportion for each species by dividing the representation of each species by the total number of Natura 2000 sites in the EU-25 countries. Comparing the REX for different species groups revealed significant differences between groups.…”
Section: Figure 1-1 the Natura 2000 Network For The Eu-28 Which Compmentioning
confidence: 99%